A post harvest handling system for melongenes (solanum melongena) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura, 2021)
32 páginas pdf. Series Miscellaneous Publication no. A2/TT-89-05; Research Division: Post Harvest Publication no. 004.